2003
DOI: 10.1111/j.1349-7006.2003.tb01523.x
|View full text |Cite
|
Sign up to set email alerts
|

Glycosylphosphatidyl inositol‐anchored protein (GPI‐80) gene expression is correlated with human thymoma stage

Abstract: Thymoma is one of the most common solid tumors in the mediastinum. Because there is no typical cell line for human thymoma, the development and use of molecular-based therapy for thymoma will require detailed molecular-genetic analysis of patients' tissues. Recent reports showed that genetic aberrations in thymoma were most frequently seen in chromosome 6q regions. We investigated the use of oligonucleotide arrays to monitor in vivo expression levels of genes in chromosome 6 regions in early- hymoma is a neopl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
0

Year Published

2004
2004
2017
2017

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 29 publications
1
6
0
Order By: Relevance
“…It has also been determined to be secreted outside of cells or tissues. GPI-80 was found to be up-regulated in thymic carcinoma (stage IV) and leukemia and has a role in the regulation of cell adhesion and migration [53][54][55]. Likewise, our results showed that GPI-80 expression was increased in lung cancer serum samples.…”
Section: Discussionsupporting
confidence: 60%
“…It has also been determined to be secreted outside of cells or tissues. GPI-80 was found to be up-regulated in thymic carcinoma (stage IV) and leukemia and has a role in the regulation of cell adhesion and migration [53][54][55]. Likewise, our results showed that GPI-80 expression was increased in lung cancer serum samples.…”
Section: Discussionsupporting
confidence: 60%
“…The lack of findings could be due to the low number of samples analyzed. We also were not able to compare expression data from tumors with that from matched normal thymus samples, which was unavailable, as in other studies [29, 47]. Finally, especially for type B2 thymomas, results may have been confounded by the presence of lymphocytic infiltrates, although we did not identify any differences in the profiles depending on the epithelial tumor cell content.…”
Section: Discussionmentioning
confidence: 80%
“…Examining tumors for alternations in gene expression is a potentially useful approach to identify the molecular differences between early-and late-stage thymomas. The advent of high-density oligonucleotide microarray technology [4], with its capacity for simultaneous monitoring of thousands of genes, provides a unique opportunity for high-throughput genetic analysis of tumor [5][6][7][8][9][10], including for thymomas [8][9][10]. Recent report showed that the gain of chromosome 1q was frequent in thymoma [11], however, responsible gene has not yet been reported.…”
Section: Introductionmentioning
confidence: 99%